Teleost Nonapeptides, Isotocin and Vasotocin Administration Released the Milt by Abdominal Massage in Male Catfish, Clarias magur - Wisdom, K. S.; Bhat, Irfan Ahmad; Pathan, Mujahidkhan A.; I., Chanu T.; Kumar, Pravesh; Babu P., Gireesh; Walke, Pravin; Nayak, Sunil Kumar; Sharma, Rupam (Frontiers in Endocrinology, 2022)
In the present work the nonapeptides i.e., isotocin and vasotocin alone or in a combination were tested in C. magur to evaluate their effect on stripping by abdominal massage. Also, we used chitosan-carbon nanotube nanocomposites to conjugate the nonapetides isotocin (abbreviated as COOH-SWCNTCSPeP) and isotocin and vasotocin (COOH-SWCNTCSPePs) with the aim of sustaining the effect for a longer duration. The conjugation of nonapeptides with nanocomposites was confirmed by Fourier-transform infrared spectroscopy (FTIR), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), Thermogravimetric analysis (TGA) and X-ray photoelectron spectroscopy (XPS). Two experiments were conducted to study the effect of naked (without nanoparticles) and conjugated nonapeptides on the milt release by stripping. Both the experiments consisted of eight treatments which included four naked groups two nanoconjugated groups and two controls. Both naked and nonconjugated formulations were successful in stripping the male catfish. The mRNA expression of selected reproductive genes was analysed to decipher the effect of nanopeptides at the molecular level. Nonapeptide treatment either naked or nanoconjugated, resulted in the upregulation of the transcript level of genes. Histological analysis revealed the concentration of spermatozoa was more in peptide injected groups than in the controls. The synergistic effects of nonapeptides and Ovatide had a positive impact on GSI. Thus, the present formulations were successful in stripping the male catfish to obtain the milt with significant reproductive success. Even though the naked groups perform better but the number of males required to fertilize the eggs in nanoconjuagted groups was smaller making it worth using for the delivery of nonapeptides.